Relationship between university readiness and academic achievement in a sample of undergraduate students - Abdul Rahman, Shukran; Sofian, Luqman Syafii (Psychology and education, 2019)
The purpose of this research was to study the level of university readiness among undergraduate university students in Malaysian Higher Learning Institutions (HLI); and to study the relationship between university readiness and academic achievement among undergraduate students. Data were gathered through responses of the University Readiness Scale from the participants who comprised of undergraduate students of one HLI. The findings answered the research questions addressed in line with the research objectives. The average level of University Readiness of undergraduate students in HLI is 77%, M=354 (SD=34.55). From the results, it is proven that University Readiness predicts academic achievement of the undergraduate students in Malaysian HLI. The results of the study are expected to help HLIs to design appropriate interventions that could prepare students to be highly ready for university education, which in turn leads to their better academic achievement. A better-prepared student will be able to acquire more competencies throughout their undergraduate programme and be able to compete healthily in the job market.